Impact of E-Commerce In India: Issues & Challenges: Navigating the Changing Landscape of E-Commerce in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The traditional shopping district is quickly being replaced by an online one. The internet is aone-stop shop where one can buy everything from a needle to a ship. In the face of increasingcompetition, established businesses and upstarts alike often come up with novel ways to market theirproducts and services. When it comes to bolstering and bettering established enterprises, electroniccommerce goes well beyond merely being an additional option. As an alternative explanation, perhaps themarket has undergone radical shifts because of the advent of online commerce. The new technologyposes serious challenges and is disrupting established corporate practises. The advent of e-commercehas opened the door to rapid economic growth in the United States. The growth of web-based users hasalso contributed to its progress. The online retail sector in our country has expanded thanks to ecommerce,which has also facilitated the expansion of the online travel sector. The purpose of thisresearch was to examine the challenges facing India's e-commerce industry and to provide a picture ofthe existing landscape and supporting factors for this sector.